Políticas de ações afirmativas no Brasil: a UFSCar Sorocaba como objeto de recorrência - Toubia, Ariane Andreia Teixeira (Universidade Federal de São Carlos, 2016)
The objective of the research was to analyze the prevailing challenges and referrals of UFSCAR-Campus Sorocaba, as the improvement and expansion support for the student from the Affirmative Action Program, from the speech of PROGRAD and PROACE representatives managers on campus.The methodological theoretical axis constitutes a preliminary bibliographic and documentary by CAPES files data level theses and dissertations of the UFSCAR, listing is relevant and approximate the thematic work. Then we chose the neoinstitutionalism as an analytical theoretical framework, whose emphasis is the study of the institution and its partners, guided by qualitative approach and this cut out the case study, considering that the UFSCar, Campus Sorocaba epistemological research site.The interviews were conducted by the structure of a semi-structured script of questions, preceded by the characterization of the respondents. We interviewed two subjects: 1 representative of the Dean of Undergraduate (PROGRAD) on campus, through the Department of Sorocaba Undergraduate Education (DeEG-Sor) and another of Dean of Community Affairs and Student (PROACE) through Department of Community Affairs and Student Sorocaba - Section of Social Care, Health and Sports (SeASSE). The interviews were conducted by the structure of a semi-structured script of questions, preceded by the characterization of the respondents. We interviewed two subjects: 1 representative of the Dean of Undergraduate (PROGRAD) on campus, through the Department of Sorocaba Undergraduate Education (DeegSer) and another of Dean of Community Affairs and Student (PROACE) through Department of Community Affairs and Student Sorocaba - Section of Social Care, Health and Sports (SeASSE). In the procedural scope, it has been used the document analysis technique (CELLARD, 2010) regarding the registrations and initiatives of the UFSCAR-Sorocaba campus. Regarding the data collection technique, the interviews have helped us to understand their statements about student support at the UFSCar-Sorocaba campus (POUPART, 2010), followed by the content analysis (BARDIN, 2009), in order to understand the voices of respondents and their returns, albeit implicit. Through the answers of respondents found that the adoption of affirmative action policies in UFSCar, not only contributed to provide greater access to historically excluded groups, as provided for students staying conditions through specific institutional support under material and food monitoring, health, transportation, among others.
Affirmative action policies in Brazil: UFSCar Sorocaba in recurrence
Keywords: Programas de ação afirmativa; Affirmative action programs; Democratização do acesso ao ensino superior; Universidade Federal de São Carlos; Democratization of access to higher education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO